Gerakan Perlawanan Menolak Pembangunan Apartemen Studi Kasus : Dusun Balirejo, Kelurahan Muja Muju, Kec Umbulharjo, Kota Yogyakarta - Fraisel Dwi Permana; David Efendi; Alam Mahadika (Aksiologi : Jurnal Pendidikan dan Ilmu Sosial, 2020)
This study aims to analyze the community's movement against the construction of an apartment located in Balirejo Hamlet, Muja Muju Village, Umbulharjo District, Yogyakarta City. This research uses qualitative analysis research methodology; the data types in this study are primary and secondary data, data obtained through documentation, direct field observations, and interviews with the affected Balirejo community and the Social Service. This study also uses secondary data collected from previous studies. The findings show that the city refuses due to: a). Social impact with the emergence of an entire society, the entry of modern society will affect culture. b). Damage to the environment, such as water resources that will be disrupted, and the situation during the development process will disrupt people's lives. And then the form of resistance from the community, namely: a). Making a petition against development that will be submitted to government officials. b) Put up billboards on the road, even in front of apartment construction. c) Conduct hearings with non-governmental organizations and government officials. d). the return of the certificate of RT and RW management was caused by not attending the community when discussing the AMDAL. There is also an impact on community life after resistance to apartment construction because people are more careful about information and irregularities in the community's social conditions: the pros and cons of development.